ITIL service operation - Steinburg, Randy (TSO (The Stationery Office) NorwichGB, 2011)
Describes best practice for managing services in supported environments. Includes guidance on achieving effectiveness and efficiency in the delivery and support of services to ensure value for the customer, the users and the service provider.